Can evolutionary insights into the brain's response to threat suggest different group interventions for perceived stress and burnout of teachers in high-risk schools?. (September 2017) - Johnson, Sharon; Naidoo, Anthony
Evolutionary brain responses to threat suggested three psychoeducational group interventions for perceived stress and burnout reduction. The interventions were based on trauma release exercises for primal brain response, transpersonal psychology for paleomammalian emotional brain functions, and transactional analysis for neomammalian cognitive brain insights. In total, 43 teachers in high-risk schools on the Cape Flats, Western Cape, South Africa, participated in one of the three different interventions, which were conducted in group sessions for 15 hr over 10 weeks. Twenty teachers were part of the control group. This pilot study, with a before-after control research design, utilised the Perceived Stress Scale for perception of stress and the Copenhagen Burnout Inventory for personal, work, and learner burnout. Multivariate comparison of trauma release exercises, transpersonal psychology, and transactional analysis intervention groups with the control group yielded significant effects for interventions within and between groups. The findings suggested that evolutionary insights into the brain's response to threat can provide a basis from which to design stress and burnout interventions.